Accordion-like swelling of layered perovskite crystals via massive permeation of aqueous solutions into 2D oxide galleries. Issue 96 (6th October 2015) - Song, Yeji; Iyi, Nobuo; Hoshide, Tatsumasa; Ozawa, Tadashi C.; Ebina, Yasuo; Ma, Renzhi; Miyamoto, Nobuyoshi; Sasaki, Takayoshi
Abstract : Platelet crystals of a layered perovskite enormously swelled in a tetrabutylammonium hydroxide solution, producing unique columnar shaped crystals with a water content of >90 wt%. Abstract : Platelet crystals of a layered perovskite showed massive accordion-like swelling in a tetrabutylammonium hydroxide solution. The permeation of the solution induced the huge expansion of the interlayer spacing as well as the crystal thickness up to 50-fold, leading to a very high water content of >90 wt%.